The influence of Islamic culture and holy Quran on performing arts: relating to sacred vocal music (LAHN) - Shokouhi, M.A.; Yusof, A. (2013)

(untitled)
Islam’s entry into the world generated a new chapter in civilization and changed direction of the history. Islamic Culture was gradually dominated on the history and civilization based on teaching Quran, in fact, holy Quran has influenced all social affairs and people’s lives. The role of Quran in history and its effects on cultures and societies especially, on art which can be regarded as an important accomplishment of human civilization. Spread of Islam religion and the formation of Islamic art caused a kind of religious convergence and cultural connection to be established between different types of arts especially, music and Islamic traditions. Generally, this paper highlights the interconnection between Islamic practices and music. This study shows that there are various forms of vocal music (Lahn) which have been generated by Islamic culture relating to the Quran. The important one is recital of Holy Quran as well as Azan (call to prayer) which is being performed several times each day in Muslim regions. For example, Music’s Muqams such as Rast, Saba, Bayat, Sigah and etc are being used for saying Azan, reading Quran and uttering Salavat in most of Islamic countries. Furthermore, there are various kinds of Dhikrs (glory and praising God, performing vocally and rhythmically) that are originated of the Quran root, such as : Lailaha ellal-lah and some beautiful names of God (Asma Al-Hosna). This article is also seeking to find out and introduce obvious examples of the links between Islamic culture and music. Moreover, some important evidences of the research will be evaluated based on main topic. The findings from the study indicate that, different types of religious vocal music have been formed systematically and expanded under the influence of the holy Quran and Islamic culture.